Are Small Agricultural Markets Recipients of World Prices? The Case of Poland - Anna Szczepańska-Przekota (Agriculture, 2023)
The increased inflation in 2021–2022, and in particular the increase in the prices of energy carriers, and thus chemical fertilizers, caused an imbalance in the market of agricultural raw materials in Poland. This problem, to a greater or lesser extent, can also be observed in other countries. Meanwhile, the issue of shaping domestic prices of agricultural commodities is one of the most important problems in a state’s food policy. This is evident in countries with strong agricultural traditions, such as Poland. Many tensions and misunderstandings between agricultural producers and the government concern the low purchase prices of agricultural commodities. Therefore, the degree of integration of the Polish price market with the world market was studied. Based on data from the wheat, beef and pork livestock markets, the impact of the world market on the Polish one was studied using VAR methodology. The analyzed data concern the years 2012–2022. It was found that the degree of price integration of various agricultural commodities is different, but always positive. The market of wheat turned out to be the most strongly price-integrated, and the markets of beef and pork livestock are slightly weaker. Such results call into question the effectiveness of aid programs for agricultural producers, as there will always be costs for the budget, which will have to be paid by the next generations, will not cause the increase in commodity prices expected by agricultural producers and will also be contrary to the principles of the free market.